Architectural Technical Debt - A Systematic Mapping Study - Sousa, Armando; Rocha, Lincoln; Britto, Ricardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Architectural Technical Debt (ATD) is one of the leading Technical Debt (TD) that causes more impact in maintaining and evolving complex software systems. We conduct a Systematic Mapping Study (SMS) to discover the main aspects of identifying and monitoring ATD items to help determine what the community has been studying about it in the last ten years. We evaluated 70 studies dating from 2012 to 2022. We find out the main types of ATD, how to measure and monitor ATD, which techniques and methods stand out in this area, the most used tools, and directions on how to calculate the cost of paying for ATD items. The results of this mapping study can help identify points that still require investigations on identifying, monitoring, and calculating the effort to fix ATD items. Furthermore, we have proposed a roadmap to aid managing Architectural Technical Debt, which provides guidance for identifying and monitoring ATD items in software systems.